Interprofessional Collaboration Dalam Pelayanan Pranikah Di Puskesmas Tegalrejo, Kota Yogyakarta - Eka Vicky Yulivantina; Gunarmi; Mufdlilah (LPPM STIKES Guna Bangsa, 2021)
Reproductive health is the start point for the development of maternal and child health that can be prepared early, even before a woman becomes pregnant and becomes a mother. The purpose of this study was to explore Interprofessional Collaboration in Premarital Services at Tegalrejo Health Center, Yogyakarta City. This study uses a qualitative method with a phenomenological approach. Data collection techniques with in-depth interviews. Data analysis using content analysis. The results showed that the implementation of interprofessional collaboration in premarital services that has been implemented at the Puskesmas Tegalrejo Yogyakarta City includes midwifery services, laboratory services, general practitioner services, nutrition services, psychological services and teeth services. Keywords: premarital, interprofessional collaboration